2003
DOI: 10.1053/joca.2002.0860
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 expression and action in chondrocytes are regulated by retinoid signaling and parathyroid hormone-related peptide (PTHrP)

Abstract: As previously indicated by mammalian studies, cRunx2 has chondrocyte pro-maturation activity. Its expression and roles are favorably modulated by retinoid signaling but are completely inhibited by PTHrP. A model integrating cRunx2 with PTHrP, Ihh and retinoid signaling and operating during skeletogenesis is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 40 publications
2
70
0
Order By: Relevance
“…The gene was then isolated from the pBluescript vector by digestion with ClaI and NotI and ligated into the RCASBP(B) L-14 or L-44 vector in the correct orientation. [25] EGFP-actin was removed from pEGFP-Actin vector (Clontech Laboratories Inc., Mountain View, CA) by digestion with NheI and BamHI and inserted into RCASBP(B) vector. RCAS replication competent viral vectors encoding GFP, constitutively active (CA)-or dominant negative (DN)-Rac-1, CA-RhoA, CA-Cdc42, GFP-Rac-1, GFPCdc42, GFP-RhoA, or EGFP-actin were transfected into DF-1 cells (ATCC).…”
Section: Rcas Virus Construction and Infectionmentioning
confidence: 99%
“…The gene was then isolated from the pBluescript vector by digestion with ClaI and NotI and ligated into the RCASBP(B) L-14 or L-44 vector in the correct orientation. [25] EGFP-actin was removed from pEGFP-Actin vector (Clontech Laboratories Inc., Mountain View, CA) by digestion with NheI and BamHI and inserted into RCASBP(B) vector. RCAS replication competent viral vectors encoding GFP, constitutively active (CA)-or dominant negative (DN)-Rac-1, CA-RhoA, CA-Cdc42, GFP-Rac-1, GFPCdc42, GFP-RhoA, or EGFP-actin were transfected into DF-1 cells (ATCC).…”
Section: Rcas Virus Construction and Infectionmentioning
confidence: 99%
“…any of several levels of regulation, including splice variation, ubiquitination, acetylation, and phosphorylation, as well as functional control through various DNA binding partners and inhibitors (reviewed in Franceschi and Xiao, 2003;Iwamoto et al, 2003;Bae and Lee, 2005;Lengner et al, 2005;Goldring et al, 2006).…”
Section: Runx2 In Larval Xenopus 1651mentioning
confidence: 99%
“…Studies in mouse and chicken have shown Runx2 mRNA to be transcriptionally active in the early cartilaginous skeleton (Inada et al, 1999;Enomoto et al, 2000Enomoto et al, , 2004EnomotoIwamoto et al, 2001;Iwamoto et al, 2003;Eames et al, 2004). However, neither species requires the gene product to be functional during early cartilage formation.…”
Section: The Evolution Of Cartilage Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic changes associated with chondrocyte hypertrophy are reported in articular chondrocytes in the context of osteoarthritis (OA). Here we report that isolated DZC have a larger cell diameter than SZC, as well as higher expression levels of ALP, and Runx2, a transcription factor necessary for chondrocyte hypertrophy and endochondral ossification (Enomoto et al, 2000;Enomoto-Iwamoto et al, 2001;Iwamoto et al, 2003;Otto et al, 1997). Overexpression of BMP2 or -7 increased cell diameter while Noggin decreased it, indicating that BMP activity was important for DZC hypertrophy.…”
Section: Bmps and Articular Chondrocyte Hypertrophymentioning
confidence: 79%